2008
DOI: 10.1086/591998
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Observational Signatures of Coronal Heating by Alfvén Waves and Nanoflares

Abstract: Alfvén waves can dissipate their energy by means of nonlinear mechanisms, and constitute good candidates to heat and maintain the solar corona to the observed few million degrees. Another appealing candidate is nanoflare reconnection heating, in which energy is released through many small magnetic reconnection events. Distinguishing the observational features of each mechanism is an extremely difficult task. On the other hand, observations have shown that energy release processes in the corona follow a power-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 47 publications
4
59
0
Order By: Relevance
“…Conversely, emission at lower temperatures is dominated by the later phase after the nanoflare has ended and such a comparison becomes possible. We find that our measured nonthermal velocities are much smaller than predicted from either the high temperature reconnection jets in the nanoflare-heated corona model, or shock heating associated with Alfvén waves, both of which suggest velocities on the order of hundreds of km s −1 (Cargill 1996;Antolin et al 2008). Models of chromospheric evaporation in response to coronal nanoflares are closer to the observations around 1 MK, but predict that non-thermal velocities should increase with temperature.…”
Section: Summary and Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Conversely, emission at lower temperatures is dominated by the later phase after the nanoflare has ended and such a comparison becomes possible. We find that our measured nonthermal velocities are much smaller than predicted from either the high temperature reconnection jets in the nanoflare-heated corona model, or shock heating associated with Alfvén waves, both of which suggest velocities on the order of hundreds of km s −1 (Cargill 1996;Antolin et al 2008). Models of chromospheric evaporation in response to coronal nanoflares are closer to the observations around 1 MK, but predict that non-thermal velocities should increase with temperature.…”
Section: Summary and Discussionsupporting
confidence: 60%
“…In contrast, hydrodynamic models of chromospheric evaporation in response to coronal nanoflares suggest nonthermal velocities of 20-36 km s −1 , increasing with temperature, at coronal loop tops in the 1.1-5.6 MK temperature range (Patsourakos & Klimchuk 2006). Models of shock heating driven by Alfvén waves also predict high velocities, >100 km s −1 (see, e.g., Antolin et al 2008), while models of Alfvén wave turbulence (van Ballegooijen et al 2011) show non-thermal velocities of 25-35 km s −1 at the tops of loops formed near 1.6 MK (Asgari- Targhi et al 2014). Furthermore, models that attempt to explain the first ionization potential (FIP) effect based on the forces acting on propagating waves suggest velocities on the order of 50-80 km s −1 (Laming 2004(Laming , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Torsional waves are intensively studied theoretically in the context of coronal heating (e.g. Antolin et al 2008;Copil et al 2008;Antolin & Shibata 2010), coronal seismology (Zaqarashvili & Murawski 2007;Verth et al 2010) and particle acceleration in solar flares (Fletcher & Hudson 2008). There is some indirect evidence of torsional standing modes (Zaqarashvili 2003) and propagating waves (Banerjee et al 2009) in spectroscopic data, and also in microwave emission (Tapping 1983;Grechnev et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated numerically that the observed spiky intensity profiles due to impulsive energy releases could be obtained from nonlinear torsional waves (see e.g. Moriyasu et al 2004;Antolin et al 2008). Taroyan (2009) showed that small-amplitude Alfvén waves can be amplified into the nonlinear regime by the presence of siphon flows in coronal loops.…”
mentioning
confidence: 99%